Construction of g-C3N4/ZIF-67 photocatalyst with enhanced photocatalytic CO2 reduction activity. (1st June 2019) - Meng, Yajuan; Zhang, Lixin; Jiu, Hongfang; Zhang, Qiaoling; Zhang, Hong; Ren, Wei; Sun, Yu; Li, Danting
Abstract: The g-C3 N4 /ZIF-67 composite has been prepared by encapsulation of ZIF-67 with g-C3 N4 . The composition of the material and the internal atomic or molecular structure were characterized by XRD and FT-IR. The morphology of the samples was observed by TEM and SEM. In addition, the samples were characterized by UV–vis DRS, PL and N2 adsorption-desorption. Compared with bulk g-C3 N4, ethanol production has increased about 3 times. The yield of ethanol decreases by about 6% after 5 cycles, which displayed cycling stability. The enhanced photocatalytic activity towards CO2 reduction was attributed to the synergistic effect of g-C3 N4 and ZIF-67, which increases the separation of electrons and holes. Graphical abstract: fx1